Preparation, characterization and drug release behavior of poly(acrylic acid-co-2-hydroxyethyl methacrylate-co-2-acrylamido-2-methyl-1-propanesulfonic acid) microgels - KAYAMAN APOHAN, NİLHAN (SPRINGER, 2011)
In this paper, Poly(acrylic acid-co-2-hydroxyethyl methacrylate-co-2-acrylamido-2-methyl-1-propanesulfonic acid (AAc-HEMA-AMPS) microgels were synthesized by using an inverse suspension polymerization technique. The increase in the AMPS content of the microgels composition caused a large increase in water uptake. The morphology of the microgels was examined by environmental scanning electron microscopy (ESEM). The AMPS containing microgels had a mean particle diameter of 10 mu m. The glass transition temperature of the microgels were examined by DSC and found that they show single Tg. Lidocaine (LD) and Methylene blue (MB) were used as model drugs for the investigation of drug release behavior of the microgels. Different drug release patterns were observed, for LD and MB loaded microgels. The release studies showed that some of the basic parameters affecting the drug release behavior of microgels were the specific and non-specific interactions between microgel and drug structure and pH of the dissolution medium. These hydrogels may be potential candidates for pH-sensitive applications.
Keywords: Suspension polymerization; Microgel; Drug release; AMPS; Acrylic acid; DIFFERENT MOLECULAR-WEIGHTS; VOLUME PHASE-TRANSITION; THERMORESPONSIVE MICROSPHERES; POLY(N-ISOPROPYLACRYLAMIDE); HYDROGELS; POLYMERS; DIFFUSION; MEMBRANES; KINETICS; WATER